How the Waltz was Won Transmutations and the Acquisition of Style in Early English Modern Ballrom Dancing. Part Two: The Waltz Regained - Buckland, Theresa Jill 1923- (Edinburgh: Edinburgh University Press, 2018)
RESUMEN: Part One of this study on the transmutation of the Victorian waltz into the modern English waltz of the early 1920s examined the labile social and choreographic climate of social dancing in London's fashionable ballrooms before, during and just after World War One. The article ended with the teachers' unsatisfactory effort to characterize the features of a distinctively modern waltz style in response to a widespread discourse to recover and adapt the dance for the contemporary English ballroom. Part Two investigates the role of club and national competitions and exhibition dancers in changing and stabilizing a waltz form and style that integrated preferred aspects of both old and new techniques, as advocated by leading waltz advocate and judge, Philip Richardson. This article brings into critical focus not only choreographic contributions by Victor Silvester and Josephine Bradley but also those of models such as Maurice Mouvet, G. K. Anderson, Georges Fontana, and Marjorie Moss whose direct influence in England outweighed that of the more famous American couple Irene and Vernon Castle. The dance backgrounds, training and inter-connections of these individuals are examined in identifying choreological and aesthetic continuities that relate to prevalent and inter-related notions of style, Englishness, art and modernity as expressed through the dancing. Taken as a whole, the two parts provide a case study of innovative shifts in popular dancing and meaning that are led through imitation and improvisation by practitioners principally from the middle class. The study also contributes to dance scholarship on cultural appropriation through concentrating on an unusual example of competition in dance being used to promote simplicity rather than virtuosity. In conclusion, greater understanding of creativity and transmission in popular social dancing may arise from identifying and interrogating the practice of agents of change and their relationships within and across their choreographic and socio-cultural contexts. PALABRAS CLAVE: English waltz, modern ballroom dancing, competition, social dance, Englishness, modernity, style, ballroom technique, Philip Richardson.
In Memory of Ivor Guest, Dance Historian Joint-Founder of the Society for Dance Research and of its Journal (14 April 1920 - 30 March 2018)